2c-11c+5=0

Simple and best practice solution for 2c-11c+5=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2c-11c+5=0 equation:


Simplifying
2c + -11c + 5 = 0

Reorder the terms:
5 + 2c + -11c = 0

Combine like terms: 2c + -11c = -9c
5 + -9c = 0

Solving
5 + -9c = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + -9c = 0 + -5

Combine like terms: 5 + -5 = 0
0 + -9c = 0 + -5
-9c = 0 + -5

Combine like terms: 0 + -5 = -5
-9c = -5

Divide each side by '-9'.
c = 0.5555555556

Simplifying
c = 0.5555555556

See similar equations:

| 2(m-3)=2(m-6) | | 5x^2-30x+100=0 | | 4(-5-x)=10-2x | | -.25x-9=.90 | | 8-h=-4 | | .28=.04(w-1.0) | | -4-6x=20 | | .28=.04(w-10) | | (3x^3)-(2x^2)= | | 0.4x-3.4=46 | | -.25-9=.90 | | 2x+11=3x+4 | | 3x^3-2x^2= | | -6m+69-9(m+1)=4m-(2m-2)-7m+6 | | 1170=68 | | (X^2+x-6)(x^2+x-2)+3= | | 0.50h-7=15 | | 9f+5(-8+3f)= | | 2[t-(2t+18)+15]=2(t+3) | | 4x+235=12x-5 | | (k,k+14)=0 | | 7y+8=1 | | 4m=12 | | 0.65x+.05(8-x)=.10(76) | | -28p-6(3-6p)=6(p-4)-2 | | 400x-100(30-x)=0 | | 8x^2-7x+4=-3x+2 | | 3x+41-6x=2-9x+3 | | t+23=15 | | 48(b+12)=63+56b | | x+.40=4 | | =3(2y+4)7-30 |

Equations solver categories